Promoting physical activity among community-dwelling seniors living in a Francophone rural area in New Brunswick: a pre-implementation qualitative study - Jbilou, Jalila; Chowdhry, Sharmeen Jalal; Frenette, Joey; Drapeau, Iza Pinette; Comeau, Ellène; Bouhtiauy, Adrien; Mekari, Saïd (Frontiers in Public Health, 2025)
ObjectivesThis study aimed to gather an in-depth understanding of Francophone community-dwelling seniors’ needs and expectations regarding physical activity to inform the design and implementation of a community-based program in a rural area in New Brunswick.MethodsUsing the socioecological model, a qualitative design was co-created and an interview guide co-developed to collect data from 24 participants, including two focus groups and 13 individual interviews. Content analyses were carried out to categorize and conceptualize the data into main and subthemes.ResultsFour major themes emerged, including the presence of challenges and barriers (community and environmental obstacles, personal challenges, and social or cultural challenges), motivators and incentives (demographics, understanding the benefits of the program, sense of belonging, and preferred physical activities), designing program infrastructure (How, What, Where, time of offer, evaluation of capabilities, feelings of familiarity), and strategies to improve recruitment and retention (what would best allow participants to join and remain in the program). The findings of this study highlighted the key challenges community-dwelling seniors living in a rural area face in participating in physical activity programs (i.e., personal issues, geographic aspects, the importance of physical capacities, and cultural trends).ConclusionWhile codesigning physical activity programs for community-dwelling seniors living in rural areas is time-consuming, it allows for a better understanding of the social and organizational assets and challenges of the target community. It also strategically contributes to managers’ ownership and community engagement of/for the program to support its implementation and promotion.